Pengaruh Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Laporan Keberlanjutan pada Perusahaan Energi - Dwi Agustina; Mahroji Mahroji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Sustainability report disclosure is an essential aspect of modern business practices, as it reflects a company’s social and environmental responsibility to stakeholders. As demands for sustainability transparency continue to increase, companies are expected not only to pursue financial gains but also to address social and environmental concerns. This study aims to examine the influence of profitability, liquidity, leverage, and firm size on the disclosure of sustainability reports. The sample consists of 24 energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, selected using purposive sampling. The data were analyzed using multiple linear regression based on secondary data from annual and sustainability reports. The findings indicate that leverage has a positive and significant effect on sustainability report disclosure, while firm size has a negative effect. Meanwhile, profitability and liquidity show no significant effect. The implication of this study is that investors tend to consider companies with high leverage, as they are more likely to disclose sustainability information as a form of legitimacy. On the other hand, the government should implement regulations in the form of incentives and sanctions to encourage large companies to consistently report their social and environmental responsibilities